2021
DOI: 10.1111/bjc.12273
|View full text |Cite
|
Sign up to set email alerts
|

Exploring service user and family perspectives of a Culturally adapted Family Intervention (CaFI) for African‐Caribbean people with psychosis: A qualitative study

Abstract: Objectives. In the UK, people of African-Caribbean background have the highest rates of psychosis and greatest inequity in mental health services of all ethnicities. National policies have highlighted the lack of evidence-based psychological interventions for this group. The aim of this study was to examine the acceptability of a novel Culturally adapted Family Intervention (CaFI) for African-Caribbean individuals diagnosed with non-affective psychosis and their relatives. Design. A qualitative design.Methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 43 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Some qualitative studies have investigated patients and relatives’ perspectives on FPE and similar interventions in single- and/or multi-family formats. These often emphasise how improved communication and a reframing of relatives understanding leads to a reduction in conflict and stress ( 18 , 19 , 21 ). Their findings resonate well with the perceived benefits and processes identified in our study, and are consistent with the theory that FPE generates a reframing of relatives understanding, which through a reduction in the level of EE leads to reduced relapse rates ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some qualitative studies have investigated patients and relatives’ perspectives on FPE and similar interventions in single- and/or multi-family formats. These often emphasise how improved communication and a reframing of relatives understanding leads to a reduction in conflict and stress ( 18 , 19 , 21 ). Their findings resonate well with the perceived benefits and processes identified in our study, and are consistent with the theory that FPE generates a reframing of relatives understanding, which through a reduction in the level of EE leads to reduced relapse rates ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Four belonged to the integrated community treatment MoC (35,39,40,42), three to the social and community connection-focused MoC (66,67,69), and one each to rehabilitation and recovery-focused (58), The identified quantitative studies (RCT and pre-post designs) suggested that focused interventions within ongoing care models impact the target, e.g., executive function (29) or treatment self-management (31)-but these changes may not impact recovery. A specific focus on the person's own goals was associated with positive recovery (33), as was greater self-direction of recovery support resources (32). Qualitative data suggested that contextual factors and non-linear experiences could derail the pursuit of goals and impede recovery (31,33), even within a well-defined, goal-pursuing intervention such as IMR (33).…”
Section: Overall Pattern Of Findingsmentioning
confidence: 96%
“…A specific focus on the person's own goals was associated with positive recovery (33), as was greater self-direction of recovery support resources (32). Qualitative data suggested that contextual factors and non-linear experiences could derail the pursuit of goals and impede recovery (31,33), even within a well-defined, goal-pursuing intervention such as IMR (33). Flexibility and ample timeframes are required for effective goal-setting to support recovery (32,33).…”
Section: Overall Pattern Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations